EVALUATING THE INFECTION POTENTIAL OF FIELD PREVAILING NEWCASTLE DISEASE VIRUS AND INFECTIOUS BRONCHITIS VIRUS ALONGWITH ASSOCIATED MICROSCOPIC CHANGES IN COMMERCIAL POULTRY - M. S. Imran; A. Aslam; M. Y. Tipu; T. Yaqub (Journal of Animal and Plant Sciences, 2019)
Newcastle disease virus (NDV) and Infectious bronchitis virus (IBV) are endemic to Pakistan. Though vaccine is being used to protect the birds from infection, outbreaks even in vaccinates are not uncommon throughout the year. Here, we assessed infectious potential of field prevailing NDV and IBV strains in broiler birds and determined a varying clinical exhibition and tissue tropism upon exposure to each of the virus either alone or in combination. At the age three week, the broiler chickens (n = 210) were divided into six groups (35 birds per group). These were group A (NDV-alone challenged), B (IBV-alone challenged), C (NDV+IBV-sequentially challenged), D (IBV+NDV-sequentially challenged), E (NDV and IBV-simultaneously challenged) and F (negative control). The birds were challenged with 10-5.76 and 10-6.03 EID50 dose of NDV and IBV, respectively. Tissue samples were taken from the infected birds after 2nd, 4th and 6th day post inoculation (dpi) for histopathology and immunohistochemistry (IHC). Clinical examination revealed a more severe form of respiratory infection in birds exposed with IBV, whereas, both respiratory and nervous signs were evident among birds infected with NDV. However, compared to birds infected with each of virus, severity of infection was much more in birds co-infected with both viruses. A variable degree of microscopic changes such as congestion and haemorrhages were observed in the trachea, lungs, proventriculus, caecal tonsil and kidney tissues. Evidenced through immunohistochemistry, the presence of antigen across various tissues of the birds indicated a wide spectrum of host tissue tropism for each of the virus where it was maximum in co-infected groups (C, D and E) than individual virus (groups A and B). The study concludes the currently prevailing strains are much pathogenic and that the presence of one virus facilitates further enhancement infection-associated tissue damage as a result of co-infection.
Keywords: Newcastle disease virus; Infectious Bronchitis virus; Co-infection; Histopathology; Immunohistochemistry